Malay Culture and Consumer Decision-Making Styles: An Investigation on Religious and Ethnic Dimensions (Jurnal Kemanusiaan, 2017)
ABSTRACTThe Malays are closely associated with the religion of Islam which constitutes a key element in Malay ethnic identity and its culture. Therefore, the main objective of this study is to investigate the Malays’ decision-making styles pertaining to shopping behavior. This study also examines the relationships between Malays’ cultural value orientations and their decision-making styles. The Consumer Style Inventory (CSI) was used to measure the Malays decision-making styles. The research findings indicated that religious factor alone is not sufficient to influence the Malays’ decision-making styles. The findings also showed that there are three decision-making styles related to Malay ethnic: perfectionistic, confused by over choice and impulsive purchase. Significant relationship was also found between religiosity and ethnicity and the shopping behavior of the Malays. The findings also revealed that Malay consumers are quite incompetent in handling product and market information, resulting in information overload and confusion. Therefore, the results of this study suggested that formal consumer education should be introduced in secondary schools in developing knowledgeable and efficient young consumers.